Induction of allopurinol resistance in Leishmania infantum isolated from dogs. - Daniel Yasur-Landau; Charles L Jaffe; Adi Doron-Faigenboim; Lior David; Gad Baneth (Public Library of Science (PLoS), 2017)
Resistance to allopurinol in zoonotic canine leishmaniasis has been recently shown to be associated with disease relapse in naturally-infected dogs. However, information regarding the formation of resistance and its dynamics is lacking. This study describes the successful in-vitro induction of allopurinol resistance in Leishmania infantum cultured under increasing drug pressure. Allopurinol susceptibility and growth rate of induced parasites were monitored over 23 weeks and parasite clones were tested at selected time points and compared to their parental lines, both as promastigotes and as amastigotes. Allopurinol resistance was formed in strains from two parasite stocks producing a 20-fold rise in IC50 along three distinct growth phases. In addition, characteristic differential clustering of single nucleotide polymorphisms (SNP) was found in drug sensitive and resistant parasite clones. Results confirm that genetic polymorphism, as well as clonal heterogeneity, contribute to in-vitro resistance to allopurinol, which is likely to occur in natural infection.